An optimal algorithm for better efficiency in WMSN for multimedia applications - Hamid Ali Abed AL‐Asadi (Wiley, 2021)
Abstract The recent trends in wireless network sensor technology are moving towards multimedia applications. Multimedia sensor nodes are difficult to communicate, but communication is necessary. Multimedia service offers both video monitoring and voice over wireless sensor networks. This causes severe problems with usage of data, power, bandwidth, energy usage and wireless sensor network deployment costs. The key restriction for the expansion of a network is the energy conservation. The nodes are distributed in the field to collect audio, video and density information so as to collect the information from sensors. The network of wireless sensors provides different layer nodes depending on their power level. In this work, Enhanced Greedy Forwarding with efficient Multi‐path and Dynamic Routing (EGFMDR) protocol was proposed and the results were compared with existing state‐of‐the‐art protocols like Ad‐hoc On‐demand Distance Vector and DYMO. Depending on how powerful they are, multi‐stage architectures were employed in various areas such as observation, military, media and traffic surveillance. They retain the effectiveness of wireless sensor network in multimedia applications. Service quality protocol parameters were analysed, and from the simulation results attained, the proposed EGFMDR protocol displays reduced end‐to‐end delay, lesser packet loss ratio and increased energy efficiency.